How The Work Environment Affects the Physical Fitness of Workers: A Survey Research on Automotive Industry in The Czech Republic - Ilona KACEROVA; Matej KRNOUL; Jan KUBR; Miroslav MALAGA (Communications of International Proceedings, 2024)
Working in the automotive industry is characterized by high complexity and places various demands on employees, which can be both physical and mental. Employees are subjected to high physical stress, which is a consequence not only of the fast pace of work but also of the constant pressure to improve the efficiency and quality of production processes. This issue is particularly relevant in the context of industrial enterprises in the Czech Republic, where increasing competitive pressure is evident in all phases of the production process. This study focuses on the results of a questionnaire survey conducted to analyze the physical overload of employees in industrial enterprises. A total of 361 people participated in the survey, providing a representative sample for assessing the current situation. The survey was conducted from October 2023 to March 2024, involving employees from various occupational sectors. It was found that 185 respondents worked in manufacturing, 102 in logistics, and 74 in administration. This study provides valuable insights into the state of physical overload in industrial enterprises and emphasizes the need to implement preventive measures and strategies to alleviate these burdens, which could lead to improved employee wellbeing and increased productivity.
Keywords: ergonomics; occupational safety; Nordic Questionnaire; physical load; human factor